FTY720/fingolimod increases NPC1 and NPC2 expression and reduces cholesterol and sphingolipid accumulation in Niemann‐Pick type C mutant fibroblasts. Issue 4 (12th January 2017) - Newton, Jason; Hait, Nitai C.; Maceyka, Michael; Colaco, Alexandria; Maczis, Melissa; Wassif, Christopher A.; Cougnoux, Antony; Porter, Forbes D.; Milstien, Sheldon; Platt, Nicholas; Platt, Frances M.; Spiegel, Sarah
Abstract : Niemann‐Pick type C (NPC) disease is a fatal neurodegenerative disorder caused by mutations in NPC1 or NPC2 with decreased functions leading to lysosomal accumulation of cholesterol and sphingolipids. FTY720/ fingolimod, used for treatment of multiple sclerosis, is phosphorylated by nuclear sphingosine kinase 2, and its active phosphorylated form (FTY720‐P) is an inhibitor of class I histone deacetylases. In this study, administration of clinically relevant doses of FTY720 to mice increased expression of NPC1 and −2 in brain and liver and decreased cholesterol in an SphK2‐dependent manner. FTY720 greatly increased expression of NPC1 and −2 in human NPC1 mutant fibroblasts that correlated with formation of FTY720‐P and significantly reduced the accumulation of cholesterol and glycosphingolipids. In agreement with this finding, FTY720 pretreatment of human NPC1 mutant fibroblasts restored transport of the cholera toxin B subunit, which binds ganglioside GM1, to the Golgi apparatus. Together, these findings suggest that FTY720 administration can ameliorate cholesterol and sphingolipid storage and trafficking defects in NPC1 mutant fibroblasts. Because neurodegeneration is the main clinical feature of NPC disease, and FTY720 accumulates in the CNS and has several advantages over available histone deacetylase inhibitors now in clinical trials, our work provides a potential opportunity for treatment of this incurable disease. —Newton, J., Hait, N. C., Maceyka, M., Colaco, A., Maczis, M., Wassif, C. A., Cougnoux, A., Porter, F. D., Milstien, S., Platt, N., Platt, F. M., Spiegel, S. FTY720/fingolimod increases NPC1 and NPC2 expression and reduces cholesterol and sphingolipid accumulation in Niemann‐Pick type C mutant fibroblasts. FASEB J . 31, 1719–1730 (2017) www.fasebj.org